Exploring the nexus of innovation management, ultraviolet irradiation, and business scale: Implications for sustainable fruit and vegetable preservation during the COVID-19 era - Assel Kydyrbekova; Kulyash Meiramkulova; Aliya Kydyrbekova; Timoth Mkilima (Journal of Innovation and Entrepreneurship, 2024)
Innovation management stands as a pivotal driver in attaining enduring sustainability in livelihoods. However, its progress can face formidable obstacles, encompassing the complexities arising from human perceptions. This research delved into the realm of innovation management within the context of fruit and vegetable preservation, with a keen focus on the potential impact of the COVID-19 pandemic and the perceptual evaluations surrounding the viability of utilizing ultraviolet (UV) irradiation for this purpose. The perceived effectiveness of UV irradiation in fruit and vegetable preservation was found to be significantly influenced by factors, such as cost, safety, and limited understanding. The respondents' preference for preserved fruits and vegetables was most significantly influenced by the elimination of pathogenic microorganisms, as indicated by a mean score of 4.6. Notably, around 50.9% of the participants demonstrated a lack of understanding regarding the use of ultraviolet irradiation as a preservation technology. In addition, approximately 21.6% of the respondents expressed disinterest in adopting ultraviolet irradiation for preserving fruits and vegetables. In contrast, a smaller percentage of participants, merely 12.3%, showed a positive inclination towards employing ultraviolet irradiation in the preservation process. Interestingly, approximately 15.2% of respondents remained undecided and did not express a definitive preference concerning their willingness to utilize ultraviolet irradiation for preserving fruits and vegetables. Notably, the analysis has revealed a compelling trend, with a substantial portion of participants (63%) perceiving medium-sized enterprises involved in fruit and vegetable processing technologies as displaying notably low levels of motivation for innovation during the COVID-19 era. A similar viewpoint was shared by 51% of respondents regarding large-scale businesses. In stark contrast, the survey has illuminated a striking disparity, as small-scale businesses exhibited significantly heightened innovation motivation at 28%, surpassing the modest 10% observed in both medium-sized and large-scale counterparts. This pronounced variation in innovation motivation across diverse business scales highlights the multifaceted impact of the pandemic on their inclination towards embracing innovation. These findings offer invaluable insights into the intricacies governing innovation management within the fruit and vegetable preservation sector amidst the challenging COVID-19 period.
Keywords: 650; COVID-19; Food security; Fruits and vegetable preservation; Innovation management; Questionnaire survey